Upgraded microwave radio thermometer input unit for remote temperature measurement of a biological object; Measurement Techniques; Vol. 60, iss. 3 - Filatov A. V. Aleksandr Vladimirovich; Anishin M. N. Maksim Nikolaevich; Gazitov S. R. Stanislav Radislavovich; Tarasov S. E. Sergey Evgenjevich; Utkin B. V. Boris Vladimirovich; Shibelgut A. A. Aleksandr Andreevich (2017, 2017)
Title screen